S07-2 Occupational exposure to endocrine-disrupting chemicals and birth weight and length of gestation: a european meta-analysis. (1st September 2016) - Burdof, A; Birks, Laura; Casas, MS; Garcia, AM; Alexander, J; Barros, H; Bergström, A; Bonde, JP; Costet, N; Danileviciute, A; Eggesbø, M; Fernández, MF; et al.
Abstract : Background: Women of reproductive age can be exposed to endocrine-disrupting chemicals (EDCs) at work and exposure to EDCs in pregnancy may affect fetal growth. Objectives: We assessed whether maternal occupational exposure to EDCs during pregnancy as classified by application of a job exposure matrix was associated with birth weight, term low birth weight (LBW), length of gestation, and preterm delivery. Methods: Using individual participant data from 133, 957 mother-child pairs in 13 European cohorts spanning births from 1994 to 2011, we linked maternal job titles with exposure to 10 EDC groups as assessed through a job exposure matrix. For each group, we combined the two levels of exposure categories (possible and probable) and compared birth outcomes with the unexposed group (exposure unlikely). We performed meta-analyses of cohort-specific estimates. Results: Eleven percent of pregnant women were classified as exposed to EDCs at work during pregnancy based on job title. Classification of exposure to one or more EDC group was associated with an increased risk of term LBW (OR 1.25, 95% CI: 1.04, 1.49), as were most specific EDC groups; this association was consistent across cohorts. Further, the risk increased with increasing number of EDC groups (OR 2.11 95% CI: 1.10, 4.06 for exposure to 4 or more EDC groups). There were few associations (p < 0.05) with the other outcomes; women holding job titles classified as exposed to bisphenol A or brominated flame retardants were at higher risk for longer length of gestation. Conclusion: Results from our large population-based birth cohort design indicate that employment during pregnancy in occupations classified as possibly or probably exposed to EDCs was associated with an increased risk of term LBW.